Pengembangan Kapasitas Petani melalui Pelatihan Farm Recording dan Digital Marketing di Desa Palon, Kabupaten Blora - Anna Fariyanti; Herawati Herawati; Yanti Nuraeni Muflikh; Suprehatin Suprehatin; Vanesha Miranda (Institut Pertanian Bogor, 2026)
Community service activities were carried out in Palon Village, Jepon District, Blora Regency, a center for beef-cattle production. The initiative responded to the continued reliance on traditional practices, especially manual financial record-keeping and product marketing, which limit efficient, evidence-based decision-making and constrain market access to mostly local buyers. The capacity-building program equipped 27 participants (farmers, livestock keepers, and fish cultivators) with practical skills in farm recording and digital marketing through a participatory approach covering preparation, training, and evaluation with pre-test and post-test. Results show substantial gains: understanding of farm recording rose from 29,63% to 48,15%, while digital marketing comprehension increased from 37.04% to 88.89%. Two primary benefits followed: participants adopted structured financial records to track costs and revenues, and they gained digital-marketing skills that expanded market reach and increased income via online platforms. These outcomes demonstrate the program’s effectiveness in enhancing financial and digital literacy and equipping farmers with managerial and marketing capabilities aligned with the demands of the digital era.